Impact of Educational Technology on Student Well-being: An Australian Perspective - Ruby King; Liam Wilson; Fathi Ben Slama (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of educational technology (EdTech) into Australian classrooms has accelerated over the past decade, especially in response to remote and blended learning demands. While EdTech has enhanced access, flexibility, and engagement in learning, growing concerns have emerged about its potential effects on student well-being. Purpose. This study investigates the multifaceted impact of educational technology on the psychological, emotional, and social well-being of secondary students in Australia. The research aims to assess both the benefits and risks associated with EdTech use, considering variables such as screen time, digital workload, connectivity, and social interaction. Method. A mixed-methods approach was employed, combining survey responses from 412 students across five states with in-depth interviews involving educators and school counselors. Results. The findings reveal a dual impact: while many students reported increased autonomy, engagement, and digital literacy, a significant proportion experienced digital fatigue, stress, and reduced peer interaction. The results also underscore the importance of digital balance and school-level support systems in mitigating negative outcomes. Conclusion. The study concludes that educational technology, when implemented thoughtfully and inclusively, can support student well-being but must be guided by holistic strategies that prioritize mental health and social connection alongside academic goals.